INOVASI METODE PEMBELAJARAN PENDIDIKAN ISLAM BERBASIS TEKNOLOGI DI ERA DIGITAL - Nila, Nila Sari; Fatmawati; Andi Abdul Hamzah (As-Sulthan Journal of Education, 2025)
This study discusses innovations in technology-based Islamic education learning methods in the rapidly developing digital era. Technology has brought significant changes to the world of education, including in the delivery of Islamic education materials. This study aims to examine the implementation of technology-based learning methods such as e-learning, educational applications, and interactive media in improving students' understanding of Islamic values. The research method used is qualitative with a case study approach in several Islamic educational institutions. Data were collected through observation, interviews with educators, and documentation analysis. The results of this study indicate that the use of technology in Islamic education learning can increase learning motivation, facilitate access to materials, and enrich more interesting and interactive delivery methods. However, challenges such as infrastructure readiness and teachers' digital competence need to be considered in implementing this method optimally. This study is expected to be a reference for educators in developing Islamic learning strategies that are relevant to the needs of the digital era.